On the V-type asteroids outside the Vesta family - II. Is (21238) 1995 WV7 a fragment of the long-lost basaltic crust of (15) Eunomia? - Carruba, V.; Michtchenko, T. A.; Lazzaro, D. (Edp Sciences S A, 2007)
Context. The V-type asteroids are associated with basaltic composition. Apart from ( 1459) Magnya, an asteroid that is clearly dynamically and mineralogically unconnected to the Vesta family, all currently known V-type asteroids are either members of the Vesta family, or are hypothesized to be former members of the dynamical family that migrated to their current orbital positions. The recent identification of ( 21238) 1995 WV7 as a V-type asteroid introduces the possibility that a second basaltic asteroid not connected with the Vesta family exists. This asteroid is on the opposite side of the 3: 1 mean motion resonance with respect to Vesta, and it would be very unlikely that a member of the Vesta family of its size (D > 5km) migrating via either the Yarkovsky effect or repeated close encounters with Vesta survived the passage through such a resonance.Aims. In this work we investigate the possibility that ( 21238) 1995 WV7 originated as a fragment of the parent body of the Eunomia family and then migrated via the interplay of the Yarkovsky effect and some powerful nonlinear secular resonances, such as the (s - s(6)) - ( g(5) - g(6)). If (15) Eunomia is, as claimed, a differentiated object whose originally pyroxene-enriched crust layer was lost in a collision that either created the Eunomia family or preceded its formation, can (21238) be a fragment of its long-lost basaltic crust that migrated to the current position?Methods. We mapped the phase space around (21238) and determined which of the nonlinear secular resonances that we identified are stronger and more capable of having caused the current difference in proper i between (21238) and members of the Eunomia family. We simulated the Yarkovsky effect by using the SWIFT-RMVSY integrator.Results. Our results suggest that it is possible to migrate from the Eunomia dynamical family to the current orbital location of ( 21238) via the interplay of the Yarkovsky effect and the (s - s6) - (g5 - g6) nonlinear secular resonance, on time-scales of at least 2.6 Gyr.Conclusions. (15) Eunomia might be the third currently known parent body for V-type asteroids.
Keywords: minor planets, asteroids; celestial mechanics